Alocação de pátios de estocagem em planos de manejo na Amazônia por meio de programação matemática - Silva, Evandro Ferreira da (2015)
The introduction of the concept of forest management accuracy has enabled the management of native forests a significant gain in accuracy and detail of exploration activities. The methodology enables the creation of a database with quantitative, qualitative and global positioning of each individual inventoried. Although this technique has reduced costs and environmental impacts, there are still some gaps that need to be improved, including the allocation of cargo handling areas, which so far is carried out arbitrary way in planning, guided by the coverage radius and modeling relief in computing environment. Given the above, the study aimed at the deterministic planning ideal places to hold the wood storage, so as to minimize the distances of drag. The study was developed in an area of 638.1783 ha, which were allocated 7896 possible storage yards to meet the demand of 1,478 exploitable individuals, taking into account the terrain elevation model, remaining individuals, permanent preservation areas and restricted areas. Finally, it performed the division of the area into sub-areas, guided by the river network. The model identifies great places allocation yards, governed by restrictions on distance and maximum volume stored. Thus, we tested four possible scenarios, evaluated the results using the Euclidean trees-yard distance and the planning of forestry. The assessment by the Euclidean distance, resulted in reductions in distances drag in all scenarios, with scenario 1 (restriction of maximum capacity and maximum distance), the scenario with improved performance, resulting in 16.81% of earnings, 21, 13%, 16.36% and 7.29% respectively, the total sum of the distances of drag, average maximum distances of drag, average distances and volume drag coefficient of variation of the courtyards. Evaluating the positioning in relation to the yard, the scenario 1 gave 20% gain, 32% and 67%, respectively for the shorter distance of 258 m intervals, between 258 and 300 m and greater than 300 m. In the analysis of post scenarios planning exploration, as the planning of forest roads, only scenario 1 showed an increase of 2.83% over the planning run, with scenario 2 which obtained better IX results in decreasing 18.48% to road construction, followed by scenario 4 (-9.35%) and scenario 3 (-0.36%). The relevance of the environmental impact was crucial to determine the best scenario, although the scenario 1 has 2,94km less than skid trails that scenario 2, holds 3,22km over construction of forest roads, so the scenario 2 obtained better performance. When analyzed the estimation of environmental impacts all scenarios have gains over run, and the stage 2 had lower estimate the generation of environmental impact, with a gain of 13.90% in relation to the planning run. Thus, it can be concluded that the scenario 2 (model with restriction maximum volume capacity and patio without restricting maximum distance carrier) had the best performance and the models proposed have been successful in relation to the planning run.